Clinical Outcomes and Factors Affecting in-Hospital Mortality among Coronary Artery Bypass Graft Patients with Intra-aortic Balloon Pump – Implications for Nursing Care - Thapasya, M. G.; Bineesh, K. R.; Preena, V.; Raj, L. Suja (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: Intra-aortic balloon pump (IABP) is the most widely used acute mechanical circulatory support device in patients undergoing coronary artery bypass graft (CABG). The objectives of the study were to assess the clinical outcomes, risk factors, and variables predictive of in-hospital mortality in these patients. Materials and Methods: Retrospective analysis of the medical records of all the 96 patients who underwent isolated on-pump CABG with IABP inserted during the period from January 2016 to January 2020 in a selected tertiary care center. The risk factors and variables predictive of in-hospital mortality were analyzed. Results: The mean age of participants was 64 ± 7.9 years. In-hospital mortality occurred in 28.2% of study subjects. Those who were hypertensive (P = 0.012, OR = 5.85, 95%CI – 1.27–26.93), pre-operative renal insufficiency (P = 0.02, OR=2.83, 95% CI – 1.12–7.12), developed new-onset atrial and or ventricular arrhythmia(P < 0.001, OR = 31.87, 95%CI - 4.09–248.28), post-operative renal insufficiency(P < 0.001, OR = 6.72, 95% CI – 2.51–18.02), and thromboembolic events (P = 0.006, OR = 6.28, 95% CI – 2.51–18.02) had a higher odds of in-hospital mortality which was statistically significant. The variables predictive of in-hospital mortality were hypertension (Adjusted OR – 7.12, 95% CI – 1.25–40.38), occurrence of new-onset arrhythmia (Adjusted OR – 22.08, 95% CI 2.54–190.48), post-operative renal insufficiency (Adjusted OR – 7.38, 95% CI – 2.17–25.09), and thromboembolic events (Adjusted OR – 2.08, 95% CI – 0.33–12.83). Conclusion: Patients requiring IABP support belong to a high-risk group with significant risk of early post-operative mortality. Assessment and understanding of patient and clinical factors affecting outcomes should be one of the core nursing responsibilities in caring these patients.